Interaction of Grafted Dextrin with a Hematite Surface: Effect of Functional Groups and Molecular Weight. Issue 31 (23rd August 2021) - Saha, Biswajit; Patra, Abhay S.; Biswas, Arijit; Mukherjee, Asim K.; Paul, Indrajit
Abstract: Reactive force field (ReaxFF) based molecular dynamics simulations were performed to study the interaction nature of grafted dextrin with hematite. Nature of interaction further explained by doing periodic density functional theory (DFT) calculations. It was observed that in presence of moisture, the polymer adsorbed on the hematite surface via hydrogen bond formation mediated by water. Upon heating, the interfacial water evaporated and boding interactions with the surface was were established. The oxygens present in the polymer backbone also took part in bonding interactions in addition to −COOH, −OH and −COOCH3 functional groups. The binding energies were estimated as −35.8 (Dextrin), −42.6 (Dextrin grafted with polyacrylic acid) and −38.0 kcal/mol (Dextrin grafted with polyacrylic acid and poly (methyl acrylate)) which indicated chemisorption and effect of molecular weight. Grafted dextrin, having higher molecular weight exhibited stronger interaction and it is anticipated that it will have better thermal stability. Binding energy estimated from DFT calculations as −34.8 kcal/mol. DFT charge density difference calculation showed that the oxygen present in the ring polymer structure also interacted with Fe d‐orbitals. Abstract : Effect of functional groups and molecular weight on the interaction of grafted dextrin with Fe2 O3 surface were presented using reactive force field (ReaxFF) simulations and density functional theory (DFT) calculations. The oxygens present in the polymer backbone also took part in bonding interaction in addition to −COOH, −OH and −COOCH3 functional groups. The binding energies were estimated as −35.8 (Dextrin), −42.6 (Dextrin grafted with polyacrylic acid) and −38.0 kcal/mol (Dextrin grafted with polyacrylic acid and poly (methyl acrylate)) which indicated chemisorption and effect of molecular weight.